Ritual and Pandemic: The Suluk Tradition of the Tarekat Naqsyabandiyah Bukittinggi Amid the Covid-19 - Adlan Sanur Tarihoran (Tamaddun, 2021)
This article analyzes the suluk tradition carried out in Surau Tarbiyah Tengah Sawah Bukittinggi during the Covid-19 Pandemic with health protocol regulations. This study uses a qualitative method. Data were collected through observation, interviews and also documentation. The data analysis technique was descriptive analytic as described by Schaltzman and Strauss from the three data interpretation models. The results showed that the Tarekat Naqsyabandiyah in performing suluk at Surau Tarbiyah Tengah Sawah Bukittinggi was still running as usual. However, during the time of Covid-19 with strict health protocols. Surau provides a place to wash hands, measure temperature, and are required to wear masks. When carrying out the suluk ritual, each individual is ensured of safety by staying at a safe distance. In the context of mysticism, the reduction in mobility does not occur. It is because suluk is a negation of mobility itself. The ritual of suluk during the pandemic is following the presentation of the murshid that the existence of performing rituals has become a means of self-quarantine for the Tarekat Naqsyabandiyah. The goal is to avoid disease and increase faith and body immunity through remembrance worship.Artikel ini bertujuan untuk mengetahui tentang tradisi suluk yang dilakukan di Surau Tarbiyah Tengah Sawah Bukittinggi pada masa Pandemi Covid-19 yang mensyaratkan adanya protokol kesehatan. Jenis penelitian ini adalah kualitatif analisi. Data dikumpulkan melalui observasi, wawancara dan juga dokumentasi. Teknik analisis data dengan deskriptif analitik sebagaimana yang dikemukan oleh Schaltzman dan Strauss dari tiga model penafsiran data. Hasil penelitian menunjukkan bahwa jamaah Tarekat Naqsabandiyah dalam melakukan suluk di Surau Tarbiyah Tengah Sawah Kota Bukittinggi masih tetap berjalan seperti biasa pada masa Covid-19 dengan protocol kesehatan yang ketat. Surau menyediakan tempat mencuci tangan, pengukur suhu dan wajib memamakai masker. Dalam hal menjaga jarak karena di tempat suluk ada tempat masing-masing jadi tentu tetap terjaga. Mengurangi mobilitas tentu tidak terjadi karena mereka bersuluk itu tidak adanya mobilitas. Ritual bersuluk pada masa Pandemi sesuai dengan penyampaian mursyid bahwa dengan adanya kegiatan bersuluk menjadi sarana karantina mandiri bagi jamaah tarekat Naqsabandiyah untuk terhindar dari penyakit serta dengan adanya zikir yang kuat meningkatkan daya iman dan imun tubuh.